2017
DOI: 10.1182/blood-2016-11-749978
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of childhood ALL using BCR-ABL1 genomic breakpoints identifies a subgroup with CML-like biology

Abstract: We used the genomic breakpoint between and genes for the DNA-based monitoring of minimal residual disease (MRD) in 48 patients with childhood acute lymphoblastic leukemia (ALL). Comparing the results with standard MRD monitoring based on immunoglobulin/T-cell receptor (Ig/TCR) gene rearrangements and with quantification of deletion, we observed very good correlation for the methods in a majority of patients; however,>20% of children (25% [8/32] with minor and 12.5% [1/8] with major- variants in the consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
90
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 55 publications
13
90
0
4
Order By: Relevance
“…We employed a multiplex long‐range PCR covering ETV6 and RUNX1 breakpoint cluster regions to allow for fusion site amplification from a minimal input of DNA from leukemic cells from initial/relapse diagnosis. Note that 77% (57/74, Figure S1) success rate achieved here is comparable to long‐range PCR assays employed for BCR‐ABL1 (81%) and other extended breakpoint regions . One additional ETV6‐RUNX1 breakpoint sequence in our cohort was identified by targeted locus amplification, which is less selective in the tested region than long‐range PCR.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…We employed a multiplex long‐range PCR covering ETV6 and RUNX1 breakpoint cluster regions to allow for fusion site amplification from a minimal input of DNA from leukemic cells from initial/relapse diagnosis. Note that 77% (57/74, Figure S1) success rate achieved here is comparable to long‐range PCR assays employed for BCR‐ABL1 (81%) and other extended breakpoint regions . One additional ETV6‐RUNX1 breakpoint sequence in our cohort was identified by targeted locus amplification, which is less selective in the tested region than long‐range PCR.…”
Section: Discussionsupporting
confidence: 56%
“…The genomic breakpoints of recurrent chromosomal translocations have been utilized as leukemia‐specific molecular markers in other specific ALL subtypes, for example, MLL rearrangements . The most recent comparison of fusion site specific MRD markers with conventional Ig/TCR rearrangements in pediatric BCR ‐ ABL1 positive ALL by Hovorkova et al underlined the feasibility and advantages of BCR ‐ ABL1 monitoring at the genomic DNA level . However, 48 ALL patients included in this analysis were treated on various protocols and the diagnostic procedures were not entirely standardized.…”
Section: Discussionmentioning
confidence: 99%
“…One of the patients, an infant with MLL-positive BCP-ALL, did not show a clonal IG rearrangement in the myeloid blasts analogous to our index patient, whereas the other patient showed the same clonal IG rearrangement For Similar to that demonstrated by 2 pediatric BCP-ALL cohorts, we demonstrated multilineage involvement of the BCR-ABL1-positive clone. 12,14 In the study by Castor et al, 12 this finding was restricted to P210 BCR-ABL1 -positive ALL, but we also demonstrated clonal involvement of the HSC/MPP compartment in patients with P190…”
Section: Described 2 Patients With Mixed Lineage Leukemia (Mll) Gene-mentioning
confidence: 74%
“…Distinguishing CML‐BP from de novo ALL can be very challenging, especially if there is no prior history of CML, although the lack of TCR beta and gamma rearrangement would favor leukemia arising in an early progenitor cell . Hovorkova et al provide data suggesting even greater complexity with a spectrum of BCR‐ABL1‐fusion‐positive B‐cell leukemias. In 20% of the cases, the BCR‐ABL1 fusion was present to variable degrees in the nonmalignant B‐ and T‐lymphoid cells and granulocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The BCR‐ABL1 fusion gene is the hallmark of chronic myelogenous leukemia (CML) and is also present in a subtype of acute lymphoblastic leukemia (ALL). Hovorkova et al provided evidence that patients presenting with BCR‐ABL1 fusion‐positive ALL might represent a spectrum of leukemia subtypes. They demonstrated that minimal residual disease (MRD) measured by the BCR‐ABL1 fusion gene polymerase chain reaction (PCR) and the immunoglobulin gene/T‐cell receptor (TCR) gene PCR was concordant in the majority of cases and that the fusion gene was confined to the lymphoid blasts.…”
Section: Introductionmentioning
confidence: 99%